2016
DOI: 10.1093/femsec/fiw142
|View full text |Cite
|
Sign up to set email alerts
|

Effects of endophytic fungi on the ash dieback pathogen

Abstract: While Hymenoscyphus fraxineus causes dieback of the European ash (Fraxinus excelsior), flowering ash (F. ornus) appears resistant to the pathogen. To date, contributions of endophytic fungi to host resistance are unknown. The following hypotheses were tested: (i) endophytic fungi enhance the resistance of F. excelsior to the pathogen; (ii) resistance of F. ornus relies on its community of endophytic fungi. Two experiments were performed. (i) The effect of exudates of ash endophytes on the germination rate of H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 38 publications
3
44
0
Order By: Relevance
“…Outside the native range of trees (Fraxinus ornus L., Fagus sylvatica L.), they harbor distinct species diversities compared to native range where more host-specific fungi can be observed [139,140]. Some dominant fungal endophytes show a strong host specificity (e.g., Venturia fraxini Aderh., [136,141,142]. These results suggest that diverse forest ecosystems, due to site-specific factors (climate, host species and latitude), have an effect on the species distribution and frequency of fungal endophytes [86,135].…”
Section: Aerial Endophytesmentioning
confidence: 77%
See 2 more Smart Citations
“…Outside the native range of trees (Fraxinus ornus L., Fagus sylvatica L.), they harbor distinct species diversities compared to native range where more host-specific fungi can be observed [139,140]. Some dominant fungal endophytes show a strong host specificity (e.g., Venturia fraxini Aderh., [136,141,142]. These results suggest that diverse forest ecosystems, due to site-specific factors (climate, host species and latitude), have an effect on the species distribution and frequency of fungal endophytes [86,135].…”
Section: Aerial Endophytesmentioning
confidence: 77%
“…However, in applying endophytes to forest management practices, diverse challenges still have to be overcome. Schlegel et al [142] suggested that the mechanism for the potential impact of endophytes and epiphytes on the ash dieback pathogen Hymenoscyphus fraxineus (T. Kowalski) Baral, Queloz & Hosoya could be through resource competition, toxin secretion or activation of plant defenses. But the long-term effect of the endophytic fungi against H. fraxineus could not be observed [142].…”
Section: Prospects For Translational Applications Of the Knowledge Fomentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, old trees that had been pollarded some decades ago are less affected than other more recently or not at all pollarded veteran trees [39]. Although some fungal ash endophytes with high in vitro antagonistic activity against H. fraxineus have been identified [93][94][95][96], an influence of endophytic mycobiomes on the health status of ash trees (i.e. the susceptibility to ash dieback) or on the establishment of the pathogen has not yet been demonstrated [77,94,96,97].…”
Section: Influencing Factorsmentioning
confidence: 99%
“…Another factor that may affect spread through the petiole is competition from endophytic fungi that may be present in the petioles (Cross et al, 2016;Scholtysik, Unterseher, Otto, & Wirth, 2013). Evidence from in vitro experiments showed that particular fungi may limit the spread (Schulz, Haas, Junker, Andrée, & Schobert, 2015;Haňáčková, Havrdová, Černý, Zahradník, & Koukol, 2017) and even the germination of H. fraxineus (Schlegel, Dubach, von Buol, & Sieber, 2016). However, their protective effect in vivo remains unclear, and H. fraxineus appears to hold an advantage due to its early and immense sporulation pressure (Cross et al, 2016).…”
Section: Discussionmentioning
confidence: 99%